To My Colleagues In the Land·Grant Universities - Mason E. Miller (Journal of Applied Communications, 1983)
"What do onsite review teams learn about our information and communication operations?" I am often asked that by ag information staff members. After 16 reviews, I think I begin to see some generalities that could be stated.